ASAH, ASIH, ASUH AS A PARENTING FRAMEWORK: DEVELOPMENT OF APSYCHOLOGICAL INSTRUMENT - Yuarini Wahyu Pertiwi; Yulia Fitriani (Adisam Publisher, 2025)
This study developed and validated a parenting instrument based on the Indonesian cultural framework of Asah, Asih, Asuh, originally articulated by Ki Hajar Dewantara, as an alternative to Western-derived measures. The theoretical foundation integrates the paradigm shift from behaviorism to attachment theory, typologies of parenting styles, and the need for balanced cognitive stimulation, emotional affection, and physical care. A quantitative approach using PLS-SEM (SmartPLS) was conducted with 415 participants aged 7–25 years. The initial item pool was derived from three dimensions, Asah (learning stimulation and values), Asih (emotional affection and attachment), and Asuh (physical provision and protection) structured on a Likert scale and reviewed by experts. Measurement model evaluation included convergent validity, discriminant validity, and internal reliability, while the structural model was assessed using R² and Q². Results indicated that 27 items met psychometric standards with outer loadings ≥ 0.70, AVE ranging from 0.61–0.65, composite reliability of 0.88–0.90, and Cronbach’s alpha between 0.84–0.86. Discriminant validity was supported by both Fornell–Larcker criteria and cross-loadings, and the model demonstrated predictive relevance (Q² > 0). Among the three dimensions, Asih exhibited the strongest reliability, underscoring the centrality of emotional support in the Indonesian cultural context. Developmental group analysis revealed age-related shifts consistent with theory: Asuh predominated among elementary school children, Asah among junior high students, and Asih among senior high school and university students. Gender differences were also evident, with females emphasizing Asih and males scoring relatively higher on Asuh. In conclusion, the Asah, Asih, Asuh construct demonstrates validity and reliability as a holistic parenting framework. Practically, the instrument is applicable for school counseling assessments, educational psychology research, family law considerations, and child protection policy planning. Recommendations include replication across regions, testing for measurement invariance, and the development of normative data by age and gender to enhance precision and applicability across diverse service settings.